DISTRIBUTION OF QT DURATION ACCORDING TO AMBULATORY ECG MONITORING DATA IN PATIENTS WITH HYPERTENSION DEPENDING ON CLINICAL MANIFESTATIONS - Tselik, N. E.; Shmidt, O. Y.; Martynenko, O. V. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 2017)
The study was carried out to identify the distribution of QTc during ECG AM depending on clinical features of EH in 82 patients. As classified shortened was considered QTс < 320 ms, as normal > 320 ms and < 440 ms, as classified prolonged was considered QTс > 440 ms. Average, maximum and minimum QTc are registered in every patient during ECG AM. The results confirm low probability of short QTc and demonstrate presence of prolonged QTc in every patient during ECG AM. The largest duration of maximal QTc have adulthood male patients with obesity III st., with low and high circadian index, with II stage and mild EH, with for the first time diagnosed EH and with EH lasting more than 10 years, with mild cardiovascular risk, with diffuse cardiosclerosis, with I and II FC and I and IIA st of HF.